Recent Experience in the Design of Music Recital Halls - Gastmeier, Bill John; Chan, Mandy (Canadian Acoustics, 2023)
Recital Halls are essential teaching/performance spaces at educational facilities for the Performing Arts. They provide flexible space for the creative training of musicians, performers, technicians and theatre staff and encourage the development of new musical compositions and are concert venues for education and profit. Variable elements can be built into their design to broaden the range of successful musical experience. This article deals with the acoustical design elements and gives insight into the design development and construction processes. Considerations of sound isolation, acoustical treatment for interior acoustical control and background HVAC sound levels are discussed.